When eating disorder attitudes and cognitions persist after weight restoration: An exploratory examination of non‐cognitive responders to family‐based treatment for adolescent anorexia nervosa. (30th January 2023) - Egbert, Amy H.; Gorrell, Sasha; Smith, Kathryn E.; Goldschmidt, Andrea B.; Hughes, Elizabeth K.; Sawyer, Susan M.; Yeo, Michelle; Lock, James; Le Grange, Daniel
Abstract: Objective: Family‐based treatment (FBT) is a well‐established intervention for adolescent anorexia nervosa (AN). Although FBT is efficacious in promoting weight gain and improvements in psychological symptoms, for some adolescents, cognitive/attitudinal recovery lags behind weight gain. This study conducted an exploratory post hoc analysis of outcomes of adolescents who achieved weight gain by the end of FBT but continued to experience elevated psychological symptoms post‐treatment. Methods: Data were drawn from two randomised controlled trials (RCTs) testing two forms of FBT (conjoint/whole family and parent‐focussed). Descriptive statistics and generalised estimating equations were used to examine differences in treatment outcomes between non‐cognitive responders (NCRs) (those who regained weight but continued to experience psychological symptoms) and full responders (FRs) (those who achieved both weight and cognitive restoration by the end of treatment) ( n = 80; 83.7% female, Agemean [SD] = 14.66 [1.73]). Results: By 12 months post‐treatment, there were no differences in weight between NCRs and FRs. However, NCRs had a slower trajectory of weight gain than FRs and continued to have elevated levels of psychological symptoms throughout the follow‐up period. Conclusions: A subset of adolescents appear to continue to experience clinically significant levels of eating pathology up to 12 months after FBT even when weight restoration is achieved. Key points: Family‐based treatment (FBT) for adolescent anorexia nervosa is efficacious in promoting weight gain and improvements in psychological symptoms, but for some adolescents, cognitive/attitudinal recovery does not accompany weight gain. Seventeen percent of participants in two randomised controlled trials (RCTs) of FBT achieved weight restoration by the end of FBT but continued to experience elevated psychological symptoms. These 'non‐cognitive responders' to FBT had a slow trajectory of weight gain and continued to have elevated levels of psychological symptoms up to 12 months after finishing FBT.